2015
DOI: 10.1111/anu.12319
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ultrafiltered fish protein hydrolysate level on growth performance, protein digestibility and mRNA expression of PepT1 in juvenile turbot (Scophthalmus maximusL.)

Abstract: The intention of the study was to investigate the effect of ultrafiltered fish protein hydrolysate (UF) level on growth, feed utilization, apparent digestibility coefficients and proximal intestine peptide transporter 1 (PepT1) mRNA level for juvenile turbot (Scophthalmus maximus L.). Experimental diets (UF‐0, UF‐5, UF‐10, UF‐15 and UF‐20) were prepared containing about 68% plant protein, and fish meal protein was, respectively, replaced by 0%, 5%, 10%, 15% and 20% UF of dietary protein. Diet PP contained abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
43
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 45 publications
(109 reference statements)
6
43
2
2
Order By: Relevance
“…Our results showed similar patterns with previous studies that intestinal PepT1 expression level peaked 2 h after re‐feeding. Furthermore, present study demonstrated that compared with the FM diet, MBM diet increased the gene expression of intestinal PepT1, which was agreed with other findings in turbot (Wei, Liang, Mu, Zheng & Xu ), but was dissimilar to previous studies on Sea Bass ( Dicentrarchus labrax ) (Terova et al . ) and Yellow Perch ( Perca flavescens ) (Ostaszewska, Dabrowski, Kamaszewski, Kwasek, Grodzik & Bierla ).…”
Section: Discussionsupporting
confidence: 88%
“…Our results showed similar patterns with previous studies that intestinal PepT1 expression level peaked 2 h after re‐feeding. Furthermore, present study demonstrated that compared with the FM diet, MBM diet increased the gene expression of intestinal PepT1, which was agreed with other findings in turbot (Wei, Liang, Mu, Zheng & Xu ), but was dissimilar to previous studies on Sea Bass ( Dicentrarchus labrax ) (Terova et al . ) and Yellow Perch ( Perca flavescens ) (Ostaszewska, Dabrowski, Kamaszewski, Kwasek, Grodzik & Bierla ).…”
Section: Discussionsupporting
confidence: 88%
“…Generally, EAAs in plant protein‐based diets can be supplemented to closely match ideal amino acid (AA) balance for optimum growth (Furuya et al, ). Previous studies reported that fish protein hydrolysates mainly containing a mixture of small peptides, and free AAs had a positive effect on the growth and feed utilization in fish fed high plant protein diets (Aksnes, Hope, Jönsson, Björnsson, & Albrektsen, ; Wei, Liang, Mu, Zheng, & Xu, ; Zheng, Liang, Yao, Wang, & Chang, ). In fact, EAAs of the formulated diets exist in the forms of free AA, peptide or protein bound (Zhang, Dabrowski, Hliwa, & Gomulka, ).…”
Section: Introductionmentioning
confidence: 99%
“…; Li, Mai, Trushenski & Wu ; Chao, Huo, Cheng, Tsai, Liao, Lee, Qin, Hsieh, Pao & Peng ; Wei et al . ). Proline is considered as a functional amino acid for fish because it is a substrate for protein synthesis, one of major extracellular components in connective tissue, the synthesis of polyamines, arginine and glutamate, antioxidative reactions and immune responses (Wu, Bazer, Burghardt, Johnson, Kim, Knabe, Li, Li, Jason, McKnight, Satterfield & Spencer ; Zhao, Han, Ren, Ma, Li & Peng ).…”
Section: Discussionmentioning
confidence: 97%
“…FPH, particularly ultrafiltered fish protein hydrolysate (UF) containing high levels of mall molecular weight compounds, is of excellent quality, in terms of amino acid profile, and may be another avenue for reducing aquaculture's dependence on fish meal (Zheng et al . ; Zheng, Liang, Yao, Wang & Chang ; Wei, Liang, Mu, Zheng & Xu ).…”
Section: Introductionmentioning
confidence: 99%